Case report: Treatment of constrictive epicarditis using the waffle procedure in a dog that had previously undergone a subtotal pericardiectomy - Saunders, Rebecca; Garnett, Steven; Lucchetti, Brittany; Jesty, Sophy (Frontiers in Veterinary Science, 2024)
A 10-year-old female spayed German Short-haired Pointer dog weighing 26.8 kg (59 lb) presented with a 2-week history of recurrent ascites. The dog had a 4-year history of idiopathic pericardial effusion causing sporadic episodes of cardiac tamponade and secondary ascites. A subtotal pericardiectomy was performed 3 months prior to presentation. The patient had done well for 2 months following this procedure, at which point the large-volume modified transudate ascites recurred, necessitating abdominocentesis every 10 days. Thoracic and abdominal computed tomography (CT) revealed no abdominal or vascular cause of ascites. Transthoracic echocardiography performed under general anesthesia showed constrictive epicarditis (visceral pericarditis) resulting in diastolic dysfunction and right-sided congestive heart failure. A sternotomy was performed for a pericardial waffle procedure or crosshatch pericardiotomy-scoring of crosshatched incisions into the thickened epicardium. Echocardiographic findings postoperatively were consistent with resolved constrictive epicarditis. At 8 months postoperatively, the dog was clinically normal and had only required one abdominocentesis one month after the waffle procedure. This case report describes the successful treatment of a dog with constrictive epicarditis using a novel surgical technique (waffle procedure) that has not yet been described in veterinary medicine.